2008
DOI: 10.1177/0093854808318624
|View full text |Cite
|
Sign up to set email alerts
|

Managing Mentally Ill Inmates in Prisons

Abstract: Mentally ill inmates now comprise a substantial portion of the prison population and pose administrative and therapeutic challenges to prison administrators and mental health professionals. Some evidence suggests that both the size of the population and the seriousness of their illnesses are increasing. Given this context, several issues are highlighted and discussed in terms of contemporary efforts to deal with mentally ill inmates. Specifically, discussion centers on the use of actuarial devices for predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…These underlying controversies are acknowledged by international authors (e.g. Adams & Ferrandino, 2008;Adshead & Sarkar, 2005;Fitzpatrick et al, 2010;Steadman, Morrissey, & Robbins, 1985;Weinberger & Sreenivasan, 1994) and will be discussed in relation to the Delphi results.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These underlying controversies are acknowledged by international authors (e.g. Adams & Ferrandino, 2008;Adshead & Sarkar, 2005;Fitzpatrick et al, 2010;Steadman, Morrissey, & Robbins, 1985;Weinberger & Sreenivasan, 1994) and will be discussed in relation to the Delphi results.…”
Section: Discussionmentioning
confidence: 90%
“…The balance between treatment and control is delicate in forensic psychiatry as acknowledged by many authors (e.g. Adams & Ferrandino, 2008;Adshead & Sakar, 2005;Fitzpatrick et al, 2010): "the treatmentcustody conflict was recognized early on by Clemmer (1940), and since that time it has become clear that there is no simple and easy solution for the conflict" (Adams & Ferrandino, 2008:917). This conflict also has an influence on the character of a forensic institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health services have historically screened out drug users and drug treatment services have historically screened out people with severe mental illness (Danzer, 2012). Judgemental attitudes towards people with co-occurring disorders by mental health staff has been well documented, with a tendency for staff to differentiate between people with a mental illness who are "deserving" of care, and people who use substances who are perceived to have "brought it on themselves" (Adams & Ferrandino, 2008;Flanagan & Lo Bue-Estes, 2005). People with co-occurring disorders have been described as "a kind of mental health under-class" with many people experiencing multiple unmet needs (Hawkings & Gilburt, 2004, p. 57).…”
Section: Understanding the Transition Experience Of People With Severmentioning
confidence: 99%
“…It has been found that overcrowding, noise, strict rules and lack of privacy in the prison environment can both exacerbate existing symptoms of mental illness, as well as cause new symptoms, such as anxiety and depression (Gelman, 2007). There is also some evidence that prisoners with severe mental illness have increased risk of self-harm and suicide that can be related to the prison environment (Adams & Ferrandino, 2008;Soderstrom, 2008). Much is still not known about the access and quality of healthcare in prison, which varies between jurisdictions.…”
Section: Prison and Post-prison Risk Environmentmentioning
confidence: 99%